Mean-Variance-Instability Portfolio Analysis: A Case of Taiwan's Stock Market - Lee, Shawin; Chang, Kuo-Ping (Management Science, 1995)
This paper applies Talpaz, Harpaz, and Penson's (THP) (Talpaz, H., A. Harpaz, J. B. Penson, Jr. 1983. Risk and spectral instability in portfolio analysis. Eur. J. Oper. Res. 14 262–269.) mean-variance-instability portfolio selection model to eight selected Taiwan stocks during 1980–89 to demonstrate how instability preference affects the traditional mean-variance frontier. In contrast to THP's finding, the empirical results show that Taiwan's high-frequency stocks have high, not low, variance. This indicates that Taiwan investors, unlike U.S. investors, prefer to speculate in high-variance stocks. The empirical results also show that short selling may increase the risk of the portfolio when the investor is instability preferred.